Decontamination of herbs and spices by gamma irradiation and low-energy electron beam treatments and influence on product characteristics upon storage. Issue 1 (1st January 2021) - Schottroff, Felix; Lasarus, Thomas; Stupak, Michal; Hajslova, Jana; Fauster, Thomas; Jäger, Henry
ABSTRACT: Culinary herbs and spices are an important sector of the food industry worldwide, but are often characterized by high levels of microbial contaminations. Therefore, irradiation is often applied to control the microbial burden. In this study, two spice decontamination technologies were compared: the established gamma irradiation as well as a newly developed low energy electron beam (LEEB) treatment. The aim of the study was to evaluate the efficacy of microbial surface inactivation for both treatments and their influence on quality attributes. Allspice berries, caraway seeds, oregano, and rosemary leaves were used as model matrices. Both treatments were shown to effectively reduce Enterococcus faecium counts below the detection limit (>3.3–5.5 log10 ). No differences in color, water activity, chlorophyll, and carotenoid contents, as well as 31 terpenoic compounds were determined between LEEB and gamma treatments in comparison to the untreated reference, for storage times of up to 105 days. Untargeted fingerprinting (SPME-GC-HRMS) showed a clustering of LEEB-treated rosemary samples, but no significant differences for the other samples.